A Flexible, Disposable Hydrogen Peroxide Sensor on Graphene Nanoplatelet-Coated Cellulose - Koshy, Obey; Pottathara, Yasir B.; Thomas, Sabu; Petovar, Barbara; Finsgar, Matjaz (Current Analytical Chemistry, 2017)
Background: In biosensors, enzymes play a crucial role in the analyte detection. However, enzyme based sensors suffer from reproducibility, tiresome immobilisation processes, high cost, and loss of enzymatic activity. In order to solve these problems, non-enzymatic detection of analytes is interesting due to the drawbacks described as regards enzymatic detection. Non-enzymatic sensor was presented in this study. Methods: In this study we functionalised a GNP by dip coating technique. Prepared samples were characterized by XRD, SEM, ATR-FTIR, contact angle analysis, UV-VIS and photoluminescence spectroscopy, and electrical measurements. Finally, analytical performance of the designed sensor was tested by cyclic voltammetry and amperometry. Results: By cyclic voltammetry it was demonstrated that by bending the sensor it still works as an analytical tool to detect H2O2. Using amperometry a linear current response as a function of the H2O2 concentration was observed in a wide concentration range. Moreover, the effect of three possible electroactive interfering species, i.e. glucose, ascorbic acid, and ethanol, on the sensor performance while reducing H2O2 was evaluated by amperometric measurement, which showed that these species are not interferences. Conclusion: The designed sensor demonstrated good performance as regards H2O2 response. We confirmed that sensor is selective towards H2O2 and that glucose, ascorbic acid and ethanol are not interferences in this case. The approach we described herein may open new avenues for using flexible graphene bio-nanosensors in a variety of wearable, implantable, real-time applications in medical and environmental monitoring.
Keywords: cyclic voltammetry